Lideranças comunitárias no contexto da pandemia: um estudo sobre identidade-metamorfose - Moraes, Gustavo Rocha de (2023)
This dissertation is a subproject of the institutional research entitled “Psychosocial Impacts and Social Technologies in Vulnerabilized Territories in the Context of the Effects of the Pandemic” of the call CNPq and MCTI nº 25/2020 and proposed an analysis of narratives of life stories of community leaders about the pandemic scenario in order to understand the process of identity as metamorphosis. It is justified in that, when conceiving the pandemic situation as a mechanism for accentuating and legitimizing critical conditions of inequality, it observes that the representative function of communities, especially those most fragile during this period, is performed by leaders (SANTOS, 2020). Since the political leader expresses a material meaning capable of materializing a collective project overflowing with personal meaning (MELO, 2012), this work consults the Marxist category of mediation to understand the collective meaning formulated by these figures in relation to the interests of their communities, as well as their future projects expressed in their narratives (ALVES, 2017a). The narrative of a life story manifests the dialectic between contexts and characters, giving power to the story, which starts to not only affect the contexts, but the narrators, given the possibility of expressing their identities, enabling understanding about the phenomena of metamorphosis in which the aspired recognition is achieved only in the manifestation of characters that takes place during the story, as the aforementioned authors discuss. To choose the narrators, the reputational method was converted into a representational method through invitations to community members to elect a restricted number of individuals understood by them as community leaders (CODATO, 2015). The scenario chosen for carrying out the research was the Central Única das Favelas (CUFA) in a city in the interior of the state of São Paulo, in accordance with the thinking of a political project proposed by Ciampa (2006) capable of promoting possibilities for attributing meaning to history as the materialization of a collective becoming committed to the material transformation of the conditions of existence. As a result of the analysis of the narratives, we were able to perceive issues relating to the recognition attributed to the deponent leadership figure, a product of a movement to bring Civil Organizations of Public Interest (OSCIPs) closer to the neoliberal democratic State, focusing on the reproduction of their representational political participation within of the community, which is understood as a State inserted in the main State; and intensified/justified during the pandemic period, configuring inclusive/exclusive identity policies (CIAMPA, 2018) (SAWAIA, 2001). In view of this, we call for a commitment to promoting mediations through the dialogic logic of communicative action capable of breaking with the process of colonization of the World of Life, since the social perspective adopted here takes advantage of society as a political and public soil, in which communicative power must be enacted in spaces that allow relationships based on reciprocal recognition equipped with communicative freedoms